Focus on the Lateral Incisural Space: Where is the Trochlear Nerve? - Herlan, Stephan; Hirt, Bernhard; Tatagiba, Marcos; Ebner, Florian H. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective To define the entrance point of the trochlear nerve in the free edge of the tentorium, giving a topographical description in relation to supratentorial and infratentorial reference points.Method The study was performed on seven formaldehyde-fixed specimens (14 sides). The distance from supratentorial and infratentorial reference points to the entrance point of the trochlear nerve into the free tentorial edge was measured.Results The cisternal segment of the trochlear nerve, the tentorial entry point, and the reference points could be clearly identified in all specimens. The assessed distances measured from the tentorial entry point of the trochlear nerve to the anterior clinoid process was 14 to 28 mm, to the posterior clinoid process was 9 to 19 mm, to the posterior lip of the inner auditory canal was 25 to 29 mm, to the posterior border of the Meckel cave was 9 to 14 mm, and to the oculomotor triangle was 5 to 16 mm.Conclusions The cisternal length of the trochlear nerve shows a marked variability and may be further distorted by tumors, whereas the entry point into the tentorium is a stable landmark. Therefore, it might be an important reference point for identifying the nerve before cutting the tentorium.
Keywords: trochlear nerve; cranial nerve IV; tentorial notch; lateral incisural space